استخدام تقنيات التنقيب في البيانات لتحسين جودة العملية التعليمية وإيصال المعرفة حالة تطبيقية: المعهد العالي لإدارة الأعمال - خازم راضي; رحال ياسر; رحمة نظرة (Latakia University Journal -Engineering Sciences Series, 2018)
The study plan is considered the Backbone of the educational process. Therefore, the more consistent the study plan is, in the meaning of well-connected according to the subject s’ order; the more enhanced the educational process becomes. This research will study the impact of applying data mining techniques on improving the quality of educational process. This will happen through presenting a model for testing the consistency of the study plan which means the accuracy of subjects’ order and determining the prerequisites. Implementing this model aims at presenting indicators that would assist the managements of educational institutions to assess their study plans in order to insure delivering the intended knowledge to the students and therefore improving the educational quality by improving its outputs. The proposed model has been implemented to test the study plans followed in the Higher Institute of Business Administration (HIBA) and it can be applied in all universities and institutes that follow the semester system. تعد الخطة الدراسية العمود الفقري للعملية التعليمية وكلما كانت الخطة الدراسية مترابطة بمعنى ترتيب المقررات كلما انعكس ذلك على تحسين جودة العملية التعليمية. سندرس في هذا البحث جدوى تطبيق بعض تقنيات التنقيب في البيانات على تحسين هذه الجودة من خلال تقديم نموذج لاختبار ترابط الخطط الدراسية بمعنى صحة ترتيب المقررات وتحديد الأسبقيات. الهدف من تطبيق النموذج هو تقديم مؤشرات تساعد إدارة المؤسسات التعليمية على تقويم الخطط الدرسية بهدف ضمان إيصال المعرفة المتوقعة للطالب، مما يسهم في تحسين جودة التعليم من خلال تحسين جودة مخرجاته. تم تطبيق النموذج المُقترح على الخطط الدراسية المُطبقة في المعهد العالي لإدارة الأعمال(HIBA) وهو قابل للتطبيق في جميع الجامعات والمعاهد التي تتبع النظام الفصلي.